A Prospective Study to Evaluate Drug Utilization Pattern and Adverse Drug Reactions in Pregnant Females at Government Medical College in Eastern Uttar Pradesh - Vaishali Maan; Prachi Chauhan; Vikas Seth; Sunny Gupta (International Journal of Science and Healthcare Research, 2026)
Background: Drug utilization studies are important for evaluating prescribing practices and promoting rational and safe medication use during pregnancy. Physiological changes during pregnancy can alter drug pharmacokinetics and pharmacodynamics and may increase susceptibility to adverse drug reactions (ADRs). However, region-specific data on drug utilization and ADRs among pregnant women in Eastern Uttar Pradesh remain limited. Objective: To evaluate drug utilization patterns and ADRs among pregnant women attending a tertiary care teaching hospital in Eastern Uttar Pradesh, with assessment of comorbidities, concomitant medication use, pregnancy outcomes, and medication-related clinical characteristics. Methods: A prospective observational study was conducted from July 2022 to December 2023 in the outpatient and inpatient departments of Government Medical College, Azamgarh, Uttar Pradesh. A total of 168 pregnant women aged 18–35 years with ultrasonographically confirmed intrauterine pregnancy were enrolled consecutively after providing written informed consent. Demographic and clinical characteristics, comorbidities, prescribed medications, dosage, route, frequency, duration, concomitant medications, and treatment-related information were recorded using a structured case record form. Drug utilization was assessed using World Health Organization prescribing indicators. Participants were prospectively monitored for suspected ADRs during pregnancy and for six months postpartum. Data were analyzed descriptively using SPSS version 23. Results: The mean age of participants was 27.30 ± 3.38 years, and the mean body weight was 59.40 ± 7.89 kg. Anaemia and hypothyroidism were among the most frequently documented comorbid conditions. Iron, folic acid, and calcium were prescribed to all participants, while their combined use constituted the most frequently observed regimen (56.5%). The mean number of drugs prescribed per prescription was 3.55 ± 1.29. Normal vaginal delivery occurred in 89.3% of participants, whereas 9.5% underwent lower-segment caesarean section and 1.2% experienced abortion. Suspected ADRs were reported in 10 participants (5.95%), with skin rash being the most frequently observed reaction (1.8%), followed by vomiting, nausea, and injection-site redness (1.2% each). Conclusion: Drug utilization in this cohort predominantly comprised routine antenatal supplementation and medications used according to documented clinical requirements. The observed frequency of suspected ADRs was low and the reported reactions were predominantly mild. Continued pharmacovigilance and systematic evaluation of medication safety during pregnancy are warranted. Keywords: Drug Utilization; Pregnancy; Pregnant Women; Drug-Related Side Effects and Adverse Reactions; Pharmacovigilance; Antenatal Care.